2023
DOI: 10.1126/sciimmunol.add9232
|View full text |Cite
|
Sign up to set email alerts
|

Group A Streptococcus induces CD1a-autoreactive T cells and promotes psoriatic inflammation

Abstract: Group A Streptococcus (GAS) infection is associated with multiple clinical sequelae, including different subtypes of psoriasis. Such post-streptococcal disorders have been long known but are largely unexplained. CD1a is expressed at constitutively high levels by Langerhans cells and presents lipid antigens to T cells, but the potential relevance to GAS infection has not been studied. Here, we investigated whether GAS-responsive CD1a-restricted T cells contribute to the pathogenesis of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…Recently, it was shown that activated GAS-responsive CD1a-reactive T cells were enriched in patients with psoriasis and were predominantly of the type 17 subtype, with a proportion of these being responsive to lysophosphatidylcholine, which is a known permissive endogenous CD1a ligand. 35 Experiments performed using TCR-transgenic T cells generated via homology-directed repair confirmed these GAS-specific CD1a-reactive T-cell responses to be TCR dependent. As mice do not express CD1a, Chen et al utilized a humanized CD1a-transgenic (hCD1a-Tg) mouse model to demonstrate the characteristic histological features of psoriasis (hyperplasia of the epidermis and dermis with pronounced rete ridges) induced by the presence of GAS.…”
Section: Psoriasismentioning
confidence: 87%
See 3 more Smart Citations
“…Recently, it was shown that activated GAS-responsive CD1a-reactive T cells were enriched in patients with psoriasis and were predominantly of the type 17 subtype, with a proportion of these being responsive to lysophosphatidylcholine, which is a known permissive endogenous CD1a ligand. 35 Experiments performed using TCR-transgenic T cells generated via homology-directed repair confirmed these GAS-specific CD1a-reactive T-cell responses to be TCR dependent. As mice do not express CD1a, Chen et al utilized a humanized CD1a-transgenic (hCD1a-Tg) mouse model to demonstrate the characteristic histological features of psoriasis (hyperplasia of the epidermis and dermis with pronounced rete ridges) induced by the presence of GAS.…”
Section: Psoriasismentioning
confidence: 87%
“…Between 5% and 10% of cutaneous T cells are CD1a-reactive. 35 In addition, CD1a-reactive T cells are found within peripheral blood and can be recruited into the skin through cutaneous homing receptors such as CLA, CCR4, CCR6 and CCR10. 36 Interestingly, unlike conventional MHC-restricted T cells, CD1a-reactive T-cell responses do not appear to always be limited to specific CD1a-lipid combinations resulting in the potential for different lipid antigens to serve as universal CD1a ligands.…”
Section: Cd1a-mediated T-cell Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…In more recent work, the interplay of bacteria‐responsive CD1a‐reactive T cells and autoreactivity was investigated in the setting of psoriasis, where Streptococcal infection could promote the generation of polyfunctional CD1a‐autoreactive T cells that produce type 1, 2, and 17 cytokines [26]. The data are consistent with earlier work showing that individuals with psoriasis have elevated frequencies of CD1a‐autoreactive and cytokine‐producing T cells in the blood and skin, explained at least in part through the activity of endogenous phospholipase A2 [22–24].…”
Section: Effector Mechanisms Of Cd1a Autoreactive T Cellsmentioning
confidence: 99%